Ethical AI surveillance in the workplace - Kritikos, Mihalis; Iphofen, Ron (Bingley, U.K. : Emerald Publishing Limited, 2023)
With surveillance at work extending into the home and the deployment of AI in the workplace already rapidly expanding, concerns have been raised about the ramifications of these developments. Blurring the boundaries between public and private spheres, digital workplace monitoring and digital activity tracking seem set to raise stress levels and undermine trust between employers and employees as they threaten to further infiltrate the world of work. Proposing a clear list of policy options, Ethical AI Surveillance in the Workplace tackles the structural challenges associated with 'wiring the labour market', including issues of control, autonomy and voice. From Data Protection Impact Assessments to regulatory sandboxes, and from establishing the right to disconnect to setting up a Code of Ethical Workplace Monitoring, the proposed paths aim to safeguard a responsible deployment of AI-powered monitoring tools within the workplace and protect employees as data subjects whose digital footprints are under constant scrutiny. Wielding the legal, regulatory and institutional tools available, this uniquely structured analysis acts as a comprehensive starting point for discussing these ever-evolving challenges and how they may shape the future of the workplace.
Introduction / Ron Iphofen Section I. Legal options -- Chapter 1. Putting the employee in the driving seat via reinforced collective agreements -- Chapter 2. Review and update the current legal framework -- Chapter 3. Introduce legislation on workplace monitoring -- Chapter 4. Introduce a penalty system and strict conditionalities -- Chapter 5. Introduce the right to obtain an explanation of the decision and challenge it -- Chapter 6. Introduce the right of transparency in workplace monitoring -- Chapter 7. Introduce the right to disconnect as a fundamental right -- Chapter 8. Introduce the right to health and safety at work in the digital space -- Chapter 9. Establish legislation for the protection of whistleblowers and the development of effective communication corridors in the workplace -- Chapter 10. Introduce review clauses on delegated/implementing acts in existing labour legislation and in any upcoming AI legislative proposals -- Chapter 11. Develop a workplace/employee-specific data governance strategy that strengthens the rights to privacy and data protection in the digital workplace -- Chapter 12. Ensure compliance with a mandatory data protection impact assessment for workplace monitoring -- Chapter 13. Redefine the concept of consent in the frame of workplace monitoring -- Chapter 14. Address psychosocial risks as an essential Part of the occupational health and safety (ohs) legal framework section ii. Governance options -- Chapter 15. Develop a code of ethical workplace monitoring -- Chapter 16. Introduce certification mechanisms and standards for ethical compliance -- Chapter 17. Set up an oversight body for workplace monitoring and other workplace governance/oversight structures -- Chapter 18. Establish an ombudsman for employment affairs and workplace monitoring -- Chapter 19. Develop and establish procedural frameworks to effectively audit workplace algorithmic systems -- Chapter 20. Set-up risk governance structures and algorithmic risk assessme
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Work environment -- Technological innovations; Artificial intelligence; Office & workplace